(untitled) (Asian Journal of Pharmaceutics (AJP), 2024)
Background: Lower respiratory tract infections (LRTIs) affect the airways and lungs, including conditions such as bronchitis, bronchiolitis, and pneumonia. These infections are a leading cause of mortality from infectious diseases worldwide, often caused by bacterial and viral pathogens. Despite their prevalence, antibiotic prescribing trends in LRTIs remain underexplored, particularly in Indian healthcare settings. Objectives: This study investigates the patterns of antibiotic prescription for LRTIs, including bronchitis, in a tertiary care teaching hospital, with a focus on monoand poly-antibiotic therapies. Methods: A cross-sectional observational study was conducted at Sri Venkateswara Institute of Medical Science, Tirupathi, India. Data were collected from 72 participants, including demographic information, clinical history, and self-medication practices. Statistical analysis was performed using the Statistical Package for Social Sciences software. The study focused on prescription patterns, gender distribution, and the types of antibiotics prescribed. Results: A greater proportion of males than females were found to suffer from LRTIs. Out of the total prescriptions analyzed, 57% were for mono-antibiotic therapy, while 7% involved poly-antibiotic therapy. LRTI diagnoses, including non-specific LRTI, pneumonia, tuberculosis, and pleural effusion, accounted for 76.28% of the cases, with 23.6% of the cases attributed to bronchitis. Augmentin and doxycycline were the two most frequently prescribed antibiotics. A comparison of the prescribed daily dose and defined daily dose of antibiotics was performed. Conclusions: The study highlights the predominant use of mono-antibiotic therapy over poly-antibiotic therapy in treating LRTIs. The findings underscore the need for better antibiotic stewardship to manage the rising number of LRTI patients. Further efforts are required to optimize treatment strategies and reduce the risk of antibiotic resistance.